Clinico-pathological Profile and Immediate Hospital Outcome of Acute Pancreatitis (Journal of Medicine, 2022)
Background: Acute pancreatitis (AP) is a significant cause of acute abdominal pain, morbidity andhospitalization. Knowing the details of the clinico-pathological presentation and outcome of the diseasemay aid the better understanding of the disease.Objective: The study was designed to assess the clinico-pathological profile and to estimate immediatehospital outcome of acute pancreatitis patients admitted into a tertiary care hospital.Materials and Methods: This hospital based cross-sectional type of observational study was conductedat Dhaka Medical College Hospital (DMCH), for one-year period (June 2018-May 2019).Total 106established cases of acute pancreatitis were included in this study. Data was analyzed by the SPSS 22Windows version and graph & chart were expressed by using SPSS 22 and MS Excel. The Result waspresented with tables and charts.Results: Among 106 patients, mean age of the patients was 42.5 ±11.3 SD (years), with male predominance(male: female-1.2:1). All of the patients complained abdominal pain (100%) while anorexia (48.1%), 43.4%had vomiting and 31.1% had fever. Regarding clinical signs, abdominal distension (45.3%), paralytic ileus(34.9%) and dehydration (43.4%) were found to be the major clinical signs. The common location of painwas in epigastric region (73.6%) with radiation to back in 20.8% patients. Pain was severe agonizing innature in 76.4% cases. Of all, gall stone disease (17.0%) was the most prevalent cause. According toAPACHE-II score, 74.5% patients had mild pancreatitis (APACHE-II